THE EFFECTIVENESS OF POWTOON BASED MEDIA ON PROJECT BASED LEARNING (PJBL) TO IMPROVE STUDENTS’ SPEAKING ABILITY - Safinatul Chairi; Mulyani Mulyani; Muliadi Muliadi (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study aims to determine the use of video animation media to improve students' speaking comprehension focused on project-based learning in eleventh grade of SMA Negeri 5 Banda Aceh teaching 2023/2024 and to find out whether the use of PowToon animation media can improve students' speaking comprehension in project-based learning in class eleven SMA Negeri 5 Banda aceh. This class consists of 20 experimental class students and 24 control class students. The author believes that the use of PowToon media can be chosen as one of the effective efforts used to overcome students' speaking comprehension in the teaching and learning process. In this study, the writer will see whether the use of PowToon media can improve students' understanding of project-based learning. From the research, the authors found that there was a significant influence on student scores before and after the experiment. The results showed that the students' post-test scores increased significantly the highest compared to the pre-test. Based on the explanation above, it can be concluded that the accepted hypothesis states that the use of video animation media can increase students' scores in understanding speech.